2011
DOI: 10.1056/nejmra1011874
|View full text |Cite
|
Sign up to set email alerts
|

Acute HIV-1 Infection

Abstract: In 2009, the United Nations Estimated that 33.2 Million People worldwide were living with human immunodeficiency virus type 1 (HIV-1) infection and that 2.6 million people had been newly infected.1 The need for effective HIV-1 prevention has never been greater. In this review, we address recent critical advances in our understanding of HIV-1 transmission and acute HIV-1 infection. Fourth-generation HIV-1 testing, now available worldwide,2,3 will allow the diagnosis of infection in many patients and may lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
508
2
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 555 publications
(532 citation statements)
references
References 95 publications
8
508
2
14
Order By: Relevance
“…During acute HIV‐1 infection, there is a vigorous immune response that is unable to contain virus replication or the establishment of latency 37. In many cases, a single transmitted/founder virus establishes infection and then evolves within the host resulting in a diverse virus population 38.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…During acute HIV‐1 infection, there is a vigorous immune response that is unable to contain virus replication or the establishment of latency 37. In many cases, a single transmitted/founder virus establishes infection and then evolves within the host resulting in a diverse virus population 38.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…Moreover, virus integration occurs early on in infection, before a protective antibody or T cell response can occur (5). Therefore, elicitation of protective antibodies before HIV-1 transmission will be required to achieve protection (6, 7). Antibodies that neutralize HIV-1 bind to the native envelope (Env) trimer, and neutralize by either blocking Env-CD4 receptor or by blocking virion fusion with host cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines are an essential preventive intervention against diseases that may be more severe amongst PLWH, such as influenza. Vaccine coverage amongst adults in Mexico is low, but no data on PLWH is available [1]. In preliminary studies from our clinic we found that all patients receive prescriptions for influenza vaccines, but we have no data on real coverage.…”
Section: P038mentioning
confidence: 99%
“…The clinical presentation is non-specific and laboratory confirmation may be inaccurate [1]. Timely and optimal identification and treatment of patients during the acute phase of HIV infection impact the long-term outcome of the individual and transmission [2].…”
Section: P039mentioning
confidence: 99%